Fantastic IgA plasma cells and where to find them. Issue 1 (27th May 2021) - Isho, Baweleta; Florescu, Alexandra; Wang, Angela A.; Gommerman, Jennifer L.
Abstract: IgA is produced in large quantities at mucosal surfaces by IgA + plasma cells (PC), protecting the host from pathogens, and restricting commensal access to the subepithelium. It is becoming increasingly appreciated that IgA + PC are not constrained to mucosal barrier sites. Rather, IgA + PC may leave these sites where they provide both host defense and immunoregulatory function. In this review, we will outline how IgA + PC are generated within the mucosae and how they subsequently migrate to their "classical" effector site, the gut lamina propria. From there we provide examples of IgA + PC displacement from the gut to other parts of the body, referencing examples during homeostasis and inflammation. Lastly, we will speculate on mechanisms of IgA + PC displacement to other tissues. Our aim is to provide a new perspective on how IgA + PC are truly fantastic beasts of the immune system and identify new places to find them.